Marcione e le spighe strappate - Norelli, Enrico (Studi e materiali di storia delle religioni, 2021)
An indirect reception of Lev. 24,5-9, the provision on the showbread, is found in Marcion's interpretation of the episode of the disciples plucking the corn during Sabbath (Lc. 6,1-5, to refer to the gospel closer to Marcion). In said episode, Jesus, in order to justify the disciples' behavior, refers to 1 Sam. 21,2-8, where David, famished, eats showbread intended for the ministers. Tertullian, adu. Marc. 4,12,5-8, summarizes the gospel passage and notes that the Marcionites saw it as evidence that Jesus wanted to "destroy" the Sabbath. The summary of the passage made by Tertullian builds a parallelism, more detailed than that in the gospel, between the disciples' and David's episodes, as both cases present the disciples' hunger and the Sabbath as setting. Through a critical examination of Tertullian's narrative and argumentation, and in particular by analysing some categories of forensic rhetoric that he uses to build his confutation, the present article tries to retrace Marcion's interpretation of the pericope. Finally, this article sketches the reading of the same episode by Irenaeus of Lyon, in order to outline the hermeneutical patterns of the three authors, referring to different theological systems. (English)